Spatial and seasonal factors are key determinants in the aggregation of helminths in their definitive hosts: Pseudamphistomum truncatum in otters (Lutra lutra). Issue 1 (January 2015) - Sherrard-Smith, E.; Perkins, S.E.; Chadwick, E.A.; Cable, J.
Graphical abstract: Highlights: Pseudamphistomum truncatum infections are highly aggregated in Lutra lutra populations. Four independent measures of parasite aggregation are assessed. Pseudamphistomum truncatum helminths are less dispersed but produce more eggs during summer. Both biotic and abiotic factors are associated with parasite abundance. Abiotic factors are most influential when describing parasite aggregation. Abstract: Parasites are typically aggregated within their host populations. The most heavily infected hosts are frequently cited as targets for optimal disease control. Yet a heavily infected individual is not necessarily highly infective and does not automatically contribute a higher proportion of infective parasitic stages than a host with fewer parasites. Here, Pseudamphistomum truncatum (Opisthorchiida) parasitic infection within the definitive otter host ( Lutra lutra ) is used as a model system. The hypothesis tested is that variation in parasite abundance, aggregation and egg production (fecundity, as a proxy of host infectivity) can be explained by abiotic (season and region) or biotic (host age, sex and body condition) factors. Parasite abundance was affected most strongly by the biotic factors of age and body condition, such that adults and otters with a higher condition index had heavier infections than sub-adults or those with a lower condition index, whilst there were no significant differences in parasite abundance among the seasons, regions (ecological regions defined by river catchment boundaries) or host sexes. Conversely, parasite aggregation was affected most strongly by the abiotic factors of season and region, which were supported by four different measures of parasite aggregation (the corrected moment estimate k, Taylor's Power Law, the Index of Discrepancy D, and Boulinier's J ). Pseudamphistomum truncatum was highly aggregated within otters, with aggregation stronger in the Midlands (England) and Wales than in the southwestern region of the United Kingdom. Overall, more parasites were found in fewer hosts during the summer, which coincides with the summer peak in parasite fecundity. Combined, these data suggest that (i) few otters carry the majority of P. truncatum parasites and that there are more infective stages (eggs) produced during summer; and (ii) abiotic factors are most influential when describing parasite aggregation whilst biotic factors have a greater role in defining parasite abundance. Together, parasite abundance, aggregation and fecundity can help predict which hosts make the largest contribution to the spread of infectious diseases.